2009
DOI: 10.1097/bsd.0b013e31818d7dc9
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Assessment of Minimally Invasive Decompression for Lumbar Spinal Canal Stenosis

Abstract: These results go toward supporting a minimally invasive bilateral decompression. Minimally invasive bilateral decompression, as opposed to a conventional medial facetectomy, preserves the facet joints as much as possible. Preserving the facet joints during the decompression should produce less postoperative instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 12 publications
1
49
0
1
Order By: Relevance
“…28 Biomechanical and laboratory results indicate that laminectomy via tubular retractors or bilateral laminotomies are associated with less destabilization than an open bilateral laminectomy. 1,5,6,12,23,34,57 In their biomechanical study, Lee et al demonstrated that bilateral laminotomy was associated with significantly less hypermobility and stiffness reduction than a full laminectomy, and they proposed that this could be attributed to preservation of the central posterior osteoligamentous structures in laminotomy. 34 In summary, minimally invasive laminectomy via tubular and similar retractors achieves effective neural decompression with simultaneous preservation of the stability of motion segments.…”
Section: 67mentioning
confidence: 99%
“…28 Biomechanical and laboratory results indicate that laminectomy via tubular retractors or bilateral laminotomies are associated with less destabilization than an open bilateral laminectomy. 1,5,6,12,23,34,57 In their biomechanical study, Lee et al demonstrated that bilateral laminotomy was associated with significantly less hypermobility and stiffness reduction than a full laminectomy, and they proposed that this could be attributed to preservation of the central posterior osteoligamentous structures in laminotomy. 34 In summary, minimally invasive laminectomy via tubular and similar retractors achieves effective neural decompression with simultaneous preservation of the stability of motion segments.…”
Section: 67mentioning
confidence: 99%
“…30 Maximal preservation of facet joints is of paramount importance to restrain progression of post-operative spinal instability. 30 Hamasaki et al, 15 within a biomechanical study based on cadaveric human lumbar spine, stated that microendoscopic ULBD approach could leave the spine more than 80% as stiff as the maiden spine. No reoperations done which may be attributable to short period of follow-up.…”
mentioning
confidence: 99%
“…Besides the pure moment form of testing, previous biomechanical investigations of the role of the facets have used compressive loading [16,25,70], eccentric loading [15,16,25], and simultaneous shear and compressive loading [53]. Of all the previous biomechanical studies that have investigated the effect of facet removal by graded, medial, or total removal--only Hamasaki et al has examined the biomechanical implications of minimally-invasive procedures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of all the previous biomechanical studies that have investigated the effect of facet removal by graded, medial, or total removal--only Hamasaki et al has examined the biomechanical implications of minimally-invasive procedures. All studies observed increases in motion with sequential or total removal of facets [15,16,18,20,25,53], and Posner et al found that there was an increase in displacement with increased removal [53].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation